Medidas provisórias tributárias e emendas parlamentares: aferição do requisito constitucional da pertinência lógico-temática a partir dos elementos da norma tributária em sentido estrito - Silva, Leidson Rangel Oliveira (2017)
The work studies the aspects related to the delimitation of the logical-thematic pertinence of the parliamentary amendments to the provisory measures in tax matters. The rules of the normative species is compared in the Constitution of other countries, seeking to understand its historical origin, and then to analyze its evolution in the Brazil legal order, identifying in an evolutionary perspective its constitutional contours, including limitations relating to tax matters. Starting from the appreciation of its legislative process of conversion, where the steps in the legislative houses are presented, it is approached the legislative control of constitutionality of the presuppositions of relevance and urgency, and of the control of the logical-thematic pertinence of the presented amendments. After approaching the exceptionality and specificity demanded of the normative species, the fundamentals of the decision of the Federal Supreme Court that determined the constitutional requirement of the thematic pertinence of the amendments are known, and then, with support in the study of the logic, to investigate the applicability of the use of the elements of the tax incidence matrix rule as a mechanism for delimiting the constitutionality of parliamentary amendments.